Kindlin1 As a Sex and Location Specific Diagnostic Marker in Gastric Cancer Patients - Mohammad Reza Abbaszadegan; Negin Taghehchian; Azadeh Aarabi; Sohrab Nozari; Ehsan Saburi; Meysam Moghbeli (Iranian Society of Pathology, 2022)
Background & Objective: Gastric cancer (GC) is considered one of the main reasons for cancer-related mortalities among Iranians. Kindlin-1 is an adhesion protein member of integrin-interacting proteins, regulating integrin activation through direct interaction with β-integrin. Therefore, kindlin-1 can be involved in the regulation of cell proliferation and adhesion. In the present study, we assessed the possible role of kindlin-1 in GC progression and metastasis.Methods:  KINDLIN1 messenger RNA (mRNA) expression was assessed in tumor tissues from 80 GC patients in comparison with normal tissues using real-time polymerase chain reaction (PCR).Results: The levels of KINDLIN1 expressions were significantly correlated with sex (P=0.05) and tumor location (P=0.002). KINDLIN1 expression was also significantly associated with lymph node metastasis among the helicobacter pylori (HP)-negative cases (P=0.001). Moreover, a significant association between age and KINDLIN1 expression was observed among the HP-positive cases (P=0.039).Conclusion: In the present study, we introduced KINDLIN1 as a location-specific marker for cardia gastric carcinoma. Moreover, it was observed that KINDLIN1 could be used as a sex-dependent diagnostic marker of GC patients.